Pengaruh Media Video Cerita Anak Terhadap Kemampuan Bercerita dan Pengembangan Moral Pada Anak Usia 4-5 Tahun di TK Aisyiyah Bustanul Athfal Kecamatan Sidoarjo - Mei Kalimatusyaro; Asmaul Husnah (THE JOER: Journal Of Education Research, 2022)
This study aims to examine: (1) The Effect of Children's Story Video Media on Storytelling Ability in Children Aged 4-5 Years at Aisyiyah Bustanul Athfal Kindergarten, Sidoarjo District, (2) The Effect of Child Story Video Media on Moral Development in Children Aged 4-5 Years in Aisyiyah Bustanul Athfal Kindergarten, Sidoarjo District, (3) The Influence of Children's Story Video Media on Storytelling Ability and Moral Development in Children Aged 4-5 Years in Aisyiyah Bustanul Athfal Kindergarten, Sidoarjo District. This study uses a Quasi-Experimental design with Nonequivalent Control Group Design. This research was carried out at TK Aisyiyah Bustanul Athfal I and III in children aged 4-5 years. The data obtained were then analyzed statistically for the Manova test (Multivariate Analysis of Variance) SPSS 20.0 for windows. The results showed that: (1) based on the Manova test (Multivariate Analysis of Variance) which produces a sig = 0.000 which is far above 0.05. Then 0.000 > 0.05 so that the hypothesis of children's story video media on storytelling ability at the age of 4-5 years of Kindergarten Aisyiyah Bustanul Athfal Sidoarjo District can be accepted, (2) based on the Manova test (Multivariate Analysis of Varians) which produces a sig value = 0.000 which well above 0.05. Then 0.000 > 0.05 so that the hypothesis of children's story video media on moral development at the age of 4-5 years of Kindergarten Aisyiyah Bustanul Athfal Sidoarjo District can be accepted, (3) based on the Manova test (Multivariate Analysis of Varians) which produces a sig value = 0.000 which well below 0.05. Then 0.000 > 0.05 so that the hypothesis of children's story video media on storytelling ability and moral development at the age of 4-5 years of Kindergarten Aisyiyah Bustanul Athfal Sidoarjo District is acceptable.